Was the Asia financial crisis avoidable? Evaluation of Asian economical system and its weakness. - Li, Rongming. (2008)
Evaluates various issues in the economic systems of countries in Asia and surrounding regions and examines the fundamental problems that caused the Asian financial crisis. It also examines the improper responses of many central banks to the crisis.